Effect of Using Hybrid Nanofluid in Thermal Management of Photovoltaic Panel in Hot Climates - Amir Komeili Birjandi; Mohammad Eftekhari Yazdi; Saeed Dinarvand; Gholam Reza Salehi; Pedram Tehrani (International Journal of Photoenergy)
Photovoltaic (PV) cells have been applied for direct conversion of solar radiation into electricity. Their performance is significantly affected by the working temperature. Due to the higher efficiency of the cells in lower temperatures, several thermal management approaches have been applied in recent years. Employing liquids as coolant is one of the efficient approaches in cooling down the PV cells. Using fluids with enhanced heat transfer properties would lead to further improvement in the output of the cells. In this paper, utilization of a hybrid nanofluid, with improved thermophysical characteristics, is numerically investigated by applying Computational Fluid Dynamics (CFD). Results revealed that by employing the low concentration hybrid nanofluid instead of water, higher efficiency and consequently electrical output are achievable. The maximum enhancement in the efficiency of the cell compared with the reference case without cooling is around 35.66% which is obtained in case of using the nanofluid with mass flow rate of 0.0002 kg/s and solar irradiation of 1000 W/m2.